(untitled) - Altucher, James (Hoboken, N.J., 2004)
Learn the successful strategies behind hedge fund investing. Hedge funds and hedge fund trading strategies have long been popular in the financial community because of their flexibility, aggressiveness, and creativity. Trade Like a Hedge Fund capitalizes on this phenomenon and builds on it by bringing fresh and practical ideas to the trading table. This book shares 20 uncorrelated trading strategies and techniques that will enable readers to trade and invest like never before. With detailed examples and up-to-the-minute trading advice, Trade Like a Hedge Fund is a unique book that will help readers increase the value of their portfolios, while decreasing risk.
Keywords: Stocks,Hedging (Finance),Index mutual funds,Cổ phần,Hàng rào (Tài chính),Chỉ số quỹ hỗ trợ